Localized Corrosion: Passive Film Breakdown vs Pit Growth Stability: Part II. A Model for Critical Pitting Temperature. Issue 9 (1st January 2018) - Li, Tianshu; Scully, J. R.; Frankel, G. S.
Abstract : Potentiostatic temperature-scanned experiments were performed on 316L stainless steel and revealed that both the measured values of critical pitting temperature (CPT) and their distribution ranges increased with the decrease of the aggressiveness of exposure conditions. Previous models for CPT cannot explain these observations, so a model for CPT is proposed based on criteria for pit growth stability with added effects of the passive film breakdown. The criterion for pit stability is assumed to be the maintenance of a critical pit solution concentration at the pit surface, which requires the maximum pit dissolution current density to be equal to or greater than the diffusion current density associated with this critical concentration. The resulting model can explain many observations of nature of the CPT. The CPT is shown not to be a single-valued critical value; instead, it is a statistically distributed value based on the detailed behavior of many pitting events. For potentiostatic measurements, the measured CPT is just the temperature at which the first stable pit forms. The commonly recognized and tightly distributed CPT is determined from the perspective of pit growth stability and it represents the temperature with the highest probability to form the first stable pit.